2008
DOI: 10.1002/chem.200801757
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of High‐Valent fac‐[99mTcO3]+ Complexes and [3+2] Cycloadditions with Alkenes in Water as a Direct Labelling Strategy

Abstract: Reported herein is a new concept for the labelling of biomolecules with small [(99m)TcO(3)](+) complexes through a [3+2] cycloaddition with alkenes for radiopharmaceutical applications. We developed convenient reactions for the synthesis of small, water stable fac-[TcO(3)(tacn-R)](+) complexes ((99)Tc and (99m)Tc, tacn = 1,4,7-triazacyclononane, R = H, -CH(2)-C(6)H(5), -CH(2)-C(6)H(4)COOH). With alkenes, these high valent [(99m)TcO(3)](+) complexes undergo [3+2] cycloaddition with formation of the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 23 publications
3
57
0
1
Order By: Relevance
“…Since, after the reaction, the resin can easily be filtered after a heterogeneous reaction, which allows for removal of excess reagents. In the presence of such polymers and a very strong tripodal ligand such as tacn, the corresponding trioxo complex was formed in moderate yield after 1 hour at 95°C as the only product from [31] rhenium analog) confirms its identity. In this particular case the compound is the 'cold' standard ( Figure 5).…”
Section: A New Labeling Strategy For Radiopharmaceutical Applicationsmentioning
confidence: 77%
See 4 more Smart Citations
“…Since, after the reaction, the resin can easily be filtered after a heterogeneous reaction, which allows for removal of excess reagents. In the presence of such polymers and a very strong tripodal ligand such as tacn, the corresponding trioxo complex was formed in moderate yield after 1 hour at 95°C as the only product from [31] rhenium analog) confirms its identity. In this particular case the compound is the 'cold' standard ( Figure 5).…”
Section: A New Labeling Strategy For Radiopharmaceutical Applicationsmentioning
confidence: 77%
“…Investigations with a variety of alkenyl-substrates showed that the reaction mechanism is strongly associatively driven and that the rates are highly dependent on the substrate used, but nearly independent of the solvent. [31] Further kinetic studies of the [ 99 TcO 3 (tacn-R)] + (R = H, bz, bz-COOH) system under pseudo-firstorder conditions showed that complexes of monosubstituted tacn-derivatives undergo a faster (3+2)-cycloaddition reaction than in the case with unsubstituted tacn. [31] This observation seems to be of critical importance when taking into account that the rate of the (3+2)-cycloaddition could be tuned by the properties of one or possibly more substituents on the tacn ligand.…”
Section: (3+2)-cycloadditions Of Fac-{tco 3 } + Complexes With Alkenesmentioning
confidence: 99%
See 3 more Smart Citations